Transformative end-to-end innovation (E2EI) in a new era for food and climate: Insights and key actions supporting institutional change - Koerner, Jana; Duda, Akshay (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
There is a broad consensus that we need to transform our innovation systems, to achieve food security for everyone, under a fast-changing climate and other global crises. End-to-end innovation (E2EI) systems carry lots of expectations, since they have been employed successfully by different sectors, including corporate, health, education. But what does it actually mean in the context of agricultural research for development? And what needs to be done, to make the different institutions and innovations systems fit for transformative E2EI?